(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The European Union (EU) is actively driving industrial transformation through initiatives such as the transition from Industry 4.0 to Industry 5.0, which emphasizes sustainability, human-centricity, and resilience. As an EU member state, Latvia aligns with these developments, leveraging Industry 5.0 to enhance efficiency, quality control, worker safety, and customer experience. While existing research highlights Industry 5.0’s positive impact on Organizational Performance (OP), concerns remain regarding its influence on the nature of Organizational Citizenship Behaviour (OCB). OCB, defined as voluntary, value-adding behaviour beyond prescribed tasks, is considered a source of competitive advantage due to its intangible nature. Despite extensive research on OCB’s relationship with OP, inconsistencies persist in OP measurement, particularly within Latvian manufacturing companies operating in the Industry 4.0 and 5.0 context. This study aims to identify relevant OP measurement indicators and OCB dimensions specific to Latvian manufacturing companies. The research is particularly relevant given the sector’s historical significance in Latvia, its decline following independence in 1991, and its recent resurgence. By focusing on Latvia, the study eliminates cross-cultural variations and provides deeper insights into industry-specific OCB-OP dynamics. A qualitative research approach is employed, using semi-structured interviews with company owners and top managers in Latvia’s manufacturing sector. Due to the sensitive nature of the study, face-to-face interviews facilitate richer insights through direct observations and explanations. Thematic content analysis is applied to analyse qualitative data. This research contributes to the existing body of knowledge by bridging the gap in OP measurement and OCB dimensionality within the evolving Industry 5.0 landscape. The findings offer practical implications for manufacturing companies, policymakers, and researchers, enhancing understanding of how OCB supports OP during the transition to Industry 5.0 principles.